Penyelesaian Sengketa Perbatasan Antara Thailand Dan Kamboja Melalui Mekanisme Asean - Elfia Farida (Masalah-Masalah Hukum, 2014)
A dispute between Thailand and Cambodia border fighting over an area of ??4.6 square kilometers around the Preah Vihear temple resolved through ASEAN mechanism. This study aims to describe, explain and analyze the ways and the efforts made ??by ASEAN. The research method used is juridical- normative. Data were analyzed qualitatively. The ways of dispute settlement that can be done is by peaceful means through dialogue, consultation, negotiation, good offices, conciliation and mediation by agreement of the parties to the dispute in accordance with the TAC. ASEAN is the effort made diplomatic efforts to avoid violence. A "shuttle diplomacy", which proved to be effective in stabilizing area of ??conflict. It also has held an informal meeting of ASEAN Foreign Ministers. Thailand and Cambodia had agreed in the three corridors, namely peace dialogue mechanism through TAC, a permanent ceasefire and ASEAN involvement in mediating the conflict.